2000
DOI: 10.2307/2648197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perceived Stress, Major Life Events and Pregnancy Attitudes on Low Birth Weight

Abstract: Interventions with pregnant women, especially those assessing perceived stress and attitudes toward the pregnancy, have the potential to improve pregnancy outcomes. Additional prospective research with pregnant women on the origins and effects of stress, including the biological effects of stress, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
2
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 15 publications
3
118
2
3
Order By: Relevance
“…Second, several cohort studies of pregnant women [16][17][18][19] have indicated that stress during pregnancy is associated with preterm and low birth weight (LBW) deliveries through established biological pathways 20 . To date, these studies have mostly emphasized the role of perceived stress and chronic stressors, such as poverty, crowding, interpersonal violence, and work-related stress, but some research has also considered the influence of severe personal life events 21,22 and even terrorism. On the basis of their review, Ohlsson and Shah 23 concluded that the World Trade Center (WTC) disaster increased the risk of LBW and small-for-gestational-age births in New York.…”
Section: Introductionmentioning
confidence: 99%
“…Second, several cohort studies of pregnant women [16][17][18][19] have indicated that stress during pregnancy is associated with preterm and low birth weight (LBW) deliveries through established biological pathways 20 . To date, these studies have mostly emphasized the role of perceived stress and chronic stressors, such as poverty, crowding, interpersonal violence, and work-related stress, but some research has also considered the influence of severe personal life events 21,22 and even terrorism. On the basis of their review, Ohlsson and Shah 23 concluded that the World Trade Center (WTC) disaster increased the risk of LBW and small-for-gestational-age births in New York.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic stress and acute stress may exert different effects on fetal development and perinatal outcomes. Several authors have reported lower birth weight and shortened gestation in children born to mothers exposed to chronic stress compared to acute stress (Chrousos and Gold 1992;Rini et al 1999;Sable and Wilkinson 2000;Wadhwa et al 1996). Likewise, there is increasing evidence that exposure to forms of toxic stress in early life alters stress responses in adulthood.…”
Section: Chronic and Acute Stressmentioning
confidence: 99%
“…By taking a holistic approach to the client assessing physiological, psychological, sociological, cultural, developmental, and spiritual areas for potential risk, it is possible to increase identification of those at risk, and intervene in an attempt to improve perinatal outcomes. Initial psychosocial assessments of pregnant women, along with interventions that address the areas causing risk, have the potential to improve pregnancy outcomes (Sable & Wilkinson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This was a significant finding because women in this group experienced no complications during gestation. Sable and Wilkinson (2000) addressed the impact of perceived stress, major life events, and pregnancy attitudes on low birth weights in a case-control study of 2378 mothers. A stepwise logistic regression model was used to control for study variables.…”
Section: Research Support Psychosocial Variablesmentioning
confidence: 99%
See 1 more Smart Citation